Sikap Introvert Sebagai Mekanisme Perlindungan Integritas Hakim: Kajian Etika Profesi Hukum - Eyda Kurnia; Zidan Hidayatullah; Audia Nuari; Fahrur Rozi; Ahmad Alwi Kindi (Jurnal Hukum Saraswati (JHS), 2025)
This research analyzes the phenomenon of judges' introverted attitudes as a protective mechanism for maintaining integrity in carrying out judicial functions. This introverted attitude serves as a foundation for understanding the boundaries of professional conduct for judges. The research methodology employs a literature study of statutory regulations, the Indonesian Judges' Code of Ethics and Conduct Guidelines (KEHI), and analysis of judicial ethics violation cases. The research findings indicate that judges' introverted attitudes play a crucial role in maintaining judicial independence and impartiality by creating professional distance that protects against conflicts of interest and external pressures. However, this attitude has limitations where excessive introversion may hinder access to justice and necessary communication in judicial processes. This research recommends the importance of achieving balance between appropriate professional conduct and proportional openness in carrying out judicial duties.